Dexamethasone Associated ST Elevation Myocardial Infarction Four Days after an Unremarkable Coronary Angiogram—Another Reason for Cautious Use of Steroids: A Case Report and Review of the Literature. (18th July 2016) - Shokr, Mohamed; Rashed, Ahmed; Lata, Kusum; Kondur, Ashok
Abstract : Drug induced myocardial infarction is a known entity with different forms of steroids linked to coronary artery disease (CAD) either through promoting its traditional risk factors, inducing coronary spasm, or by other unidentified mechanisms. Dexamethasone is known to promote an atherogenic and hypercoagulable state. We report a case of a 75-year-old woman who had ST elevation myocardial infarction (STEMI) associated with dexamethasone use just 4 days following an angiogram showing minor luminal irregularities.